2000
DOI: 10.1074/jbc.m001929200
|View full text |Cite
|
Sign up to set email alerts
|

α-Catenin Inhibits β-Catenin Signaling by Preventing Formation of a β-Catenin·T-cell Factor·DNA Complex

Abstract: ␣-Catenin and ␤-catenin link cadherins to the cytoskeleton at adherens junctions. ␤-Catenin also associates with members of the T-cell factor (Tcf) family of transcription factors, and mutations in ␤-catenin lead to activation of Tcf-dependent transcription and increased cell growth. Although the loss of ␣-catenin expression can also promote cell growth, the role of endogenous ␣-catenin in ␤-catenin signaling is unclear. Here we show that loss of ␣-catenin expression in a colon cancer cell line correlates with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
90
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 44 publications
15
90
2
Order By: Relevance
“…23 Ctnna1 (a-catenin) also can block the interaction between the b-catenin/Tcf/DNA complex. 24 In addition, in agreement with our result, the reduced expression of a-catenin has been reported in several human cancers. 25 These data led us to investigate the abnormality of b-catenin protein expression in radiation-induced OS (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…23 Ctnna1 (a-catenin) also can block the interaction between the b-catenin/Tcf/DNA complex. 24 In addition, in agreement with our result, the reduced expression of a-catenin has been reported in several human cancers. 25 These data led us to investigate the abnormality of b-catenin protein expression in radiation-induced OS (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Upregulation of alpha-catenin could be an important mechanism of anti-carcinogenicity since alpha-catenin can act as an invasion suppressor [67]. Alpha-catenin expression in colon cancer cells is associated with an inhibition of TCF-dependent transcription [68]. Also, overexpression of plakophilin 2 in SW480 cells (human colon carcinoma cell line) caused an increase in β-catenin/TCF signaling [69].…”
Section: Discussionmentioning
confidence: 99%
“…Transfection with ␣-catenin targeted to the nucleus inhibits transcription activity to the same extent as nontargeted ␣-catenin. Because ␣-catenin associated stably with the ␤-catenin-TCF complex, it was proposed that ␣-catenin may inhibit ␤-catenin-TCF transcription either by preventing DNA binding or by altering the ␤-catenin-TCF interactions with other proteins that regulate transcription in vivo (Giannini et al, 2000). Factors that regulate nuclear entry of ␣-catenin would link signaling events in the cytoplasm to ␤-catenin-dependent transcription in the nucleus.…”
Section: Nuclear Localization Of ␣-Cateninmentioning
confidence: 99%
“…Factors that regulate nuclear entry of ␣-catenin would link signaling events in the cytoplasm to ␤-catenin-dependent transcription in the nucleus. Giannini et al (2000), using immunofluorescence and confocal microscopy, reported nuclear localization of ␣-catenin in the cell line SW480 but not in HCT 116. However, in that study, confluent monolayers of HCT116 were examined, whereas the present study found ␣-catenin nuclear localization only in dispersed cells.…”
Section: Nuclear Localization Of ␣-Cateninmentioning
confidence: 99%